PENGELOLAAN KEUANGAN DAERAH YANG BAIK SEBAGAI SALAH SATU UNSUR DARI PENGAWASAN: Good Regional Financial Management as an Element of Supervision - Bobby Segah; Kaharap Kaharap (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2022)
This paper aims to see and study and describe several things related to transparent and accountable regional financial management as one of the elements of supervision. Transparently, in order to provide clarity in analyzing the above statement, the data in this paper were collected through a literature study, and in this paper, we only look in general terms at good and transparent financial management. Based on the creativity and ability of local governments to manage finances, by utilizing existing resources. In addition, local governments also innovate in terms of regional financial management, especially exploring good sources by doing several things such as increased supervision at each reception post so that it can reduce revenue leakage, Collecting data on potential sources of existing revenue as well as exploring new potential, Intensify billing and increase monitoring, Implement Cash Management. Regarding the implementation of transparent regional financial management, the regional government has submitted its financial reports periodically on its website which can be accessed directly by the entire community, so that every community also has wide enough access to find out the development of funds in the area, especially at the government level. Submission of financial reports like this to the general public is an indication of government transparency in the use of regional revenue and expenditure budgets.